2016
DOI: 10.1002/aqc.2663
|View full text |Cite
|
Sign up to set email alerts
|

Diving for science ‐ science for diving: volunteer scuba divers support science and conservation in the Mediterranean Sea

Abstract: 1. Recreational diving engages 20 million people worldwide. Most of the literature refers to tropical destinations but at least 1 million dives per year take place in Mediterranean marine protected areas (MPAs).2. Divers may negatively affect underwater habitats. However, if effectively engaged, they can contribute to science, territorial management and more sustainable local economies.3. During 2006-2014, volunteers trained by the not-for-profit organization Reef Check Italia (RCI) completed 24 714 observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 70 publications
3
75
0
Order By: Relevance
“…Anchoring must therefore be banned, and recreational boating regulated (Venturini et al, ). Pleasure crafts could be allowed to moor to buoys installed for this purpose, which would be especially useful for diving centres: if correctly managed, scuba‐diving tourism represents a sustainable activity that generates revenue and supports local communities (Lucrezi et al, ), and may even actively support conservation (Cerrano, Milanese, & Ponti, ). Inspections in 2016 showed that derelict fishing gear caused a severe impact on epibenthic communities, suggesting that all forms of bottom fishing must be banned and recreational fishing should be strictly regulated (Venturini, Campodonico, Cappanera, Fanciulli, & Cattaneo‐Vietti, ).…”
Section: Discussionmentioning
confidence: 99%
“…Anchoring must therefore be banned, and recreational boating regulated (Venturini et al, ). Pleasure crafts could be allowed to moor to buoys installed for this purpose, which would be especially useful for diving centres: if correctly managed, scuba‐diving tourism represents a sustainable activity that generates revenue and supports local communities (Lucrezi et al, ), and may even actively support conservation (Cerrano, Milanese, & Ponti, ). Inspections in 2016 showed that derelict fishing gear caused a severe impact on epibenthic communities, suggesting that all forms of bottom fishing must be banned and recreational fishing should be strictly regulated (Venturini, Campodonico, Cappanera, Fanciulli, & Cattaneo‐Vietti, ).…”
Section: Discussionmentioning
confidence: 99%
“…Epibenthic sessile assemblages inside and outside P. clavata forests were investigated by applying a multifactorial sampling design. Nine sites were randomly selected among those with a high abundance of P. clavata , as reported in the Reef Check database (Cerrano, Milanese, & Ponti, ; see Appendix S1, Figure S1.1) (Figure ). At each site four areas inside and four areas outside the P. clavata forests, with similar orientation, inclination, and depth (±3 m), were randomly selected.…”
Section: Methodsmentioning
confidence: 99%
“…Divers are one of the main volunteer groups participating in marine CS projects (Thiel et al, 2014) and one of the most interested marine user groups (Martin et al, 2016b). However, little knowledge exists about the profiles of divers who join CS projects (Cerrano et al, 2016) and even less information is available about those who are not joining. Here we present a study of different types of divers in Chile, their background characteristics, diving experience level and their preferences for different ways of participating in marine CS.…”
Section: Importance Of Public Preferences For Participation In Citizementioning
confidence: 99%
“…Existing evidence suggests that divers participating in CS projects have a high education level, previous interest in science and high diving experience (Arvanitidis et al, 2011;Cerrano et al, 2016;Lucrezi et al, 2018). Martin et al (2016b) studied public interest in marine CS and found that SCUBA divers have the highest level of interest in CS among many marine user types.…”
Section: Lack Of Information About the Diversity Of Divers In Citizenmentioning
confidence: 99%